Cover Picture: Squalenyl Hydrogen Sulfate Nanoparticles for Simultaneous Delivery of Tobramycin and an Alkylquinolone Quorum Sensing Inhibitor Enable the Eradication of P. aeruginosa Biofilm Infections (Angew. Chem. Int. Ed. 26/2020). Issue 26 (28th April 2020) - Ho, Duy‐Khiet; Murgia, Xabier; De Rossi, Chiara; Christmann, Rebekka; Hüfner de Mello Martins, Antonio G.; Koch, Marcus; Andreas, Anastasia; Herrmann, Jennifer; Müller, Rolf; Empting, Martin; Hartmann, Rolf W.; Desmaele, Didier; et al.
Abstract : Simultaneous delivery of tobramycin and alkylquinolone inhibitors by a self‐assembling nanoparticle system based on squalenyl hydrogen sulfate (SqNPs) is an optimal therapeutic against P. aeruginosa biofilm infections. As described by C.‐M. Lehr et al. in their Communication on page 10292, the drug‐loaded SqNPs show improved biofilm penetration and enhanced efficacy in relevant biological barriers (mucin/human tracheal mucus, biofilms), leading to complete eradication of P. aeruginosa biofilms at 16‐fold lower tobramycin concentration than tobramycin alone.